2020
DOI: 10.1007/s13318-020-00634-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risk of Food-Drug Interactions: Citrus Polymethoxyflavones and Flavanones as Inhibitors of the Organic Anion Transporting Polypeptides (OATP) 1B1, 1B3, and 2B1

Abstract: Background and Objectives Citrus flavonoids are not only components of daily nutrition, they are also promoted as dietary supplements and are important ingredients in traditional medicines. Interactions of flavonoids with synthetic drugs represent an often neglected issue. We therefore investigated in vitro whether the polymethoxyflavones nobiletin, sinensetin, and tangeretin and the flavonoid rutinosides didymin, hesperidin, and narirutin can inhibit human organic anion transporting polypeptides (OATP) 1B1, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…13,19,20 Recently, Bajraktari-Sylejmani et al have shown that narirutin inhibits OATP2B1-mediated 4′,5′-dibromofluorescein transport. 29 However, they did not analyze the inhibitory kinetics of narirutin in detail. In addition, it has not been reported to have inhibitory effects on OATP1A2.…”
Section: ■ Discussionmentioning
confidence: 99%
“…13,19,20 Recently, Bajraktari-Sylejmani et al have shown that narirutin inhibits OATP2B1-mediated 4′,5′-dibromofluorescein transport. 29 However, they did not analyze the inhibitory kinetics of narirutin in detail. In addition, it has not been reported to have inhibitory effects on OATP1A2.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Although the small effect on OATP1B1 is most likely not relevant in vivo , because systemic concentrations of GBPA are too low for inhibition of this liver-specific uptake transporter, the potency for intestinal OATP2B1 inhibition is clearly high enough to be of clinical relevance. Inhibition of this uptake transporter represents a typical feature of several citrus flavonoids [ [38] , [39] , [40] ] and can lead to decreased bioavailability of respective substrates as already postulated e.g. for aliskiren [ 41 , 42 ], celiprolol [ 43 ], and rosuvastatin [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin and its metabolite hesperetin showed an inhibitory effect on the activities of CYP1A, CYP1B1, CYP3A4, and P-gp 259 , 260 . Tangeretin exerts an inhibitive effect on OATP2B1 261 , but can significantly increase the mRNA expression of CYP3A4 by regulating PXR 262 . Nobiletin is both a CYP1A2 inhibitor and inducer, while tangeretin is an inducer of CYP3A4 263 .…”
Section: Tcms For the Treatment Of Covid-19 Infectionsmentioning
confidence: 99%